KOMPETENSI PEGAWAI BAGIAN OTONOMI DAERAH TERHADAP PENYUSUNAN LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH KABUPATEN KUTAI TIMUR - Fl Sudiran Ibnu Tahiyatul Muhammad Maulidan (ADMINISTRASI PUBLIK, 2017)
This study is intended to determine the competence of employees in Section Autonomous Region Secretariat of the East Kutai Regency in preparing the reports of Regional Government, therefore, the researchers formulated the hypothesis "Allegedly the competence of employees in Section Autonomous Region Secretariat of the East Kutai Regency in preparing the reports of Regional Government is good".The timing of the research was conducted in August 2016 until the month of November 2016 for 3 (three) months. This research is a descriptive study, with qualitative analysis, the data obtained through direct observation in the field and distributing questionnaires to the respondents with a sample size of 20 (twenty) of respondents.Based on qualitative analysis used is known the value of employee competence in Section Autonomous Region East Kutai Regency Secretariat amounted to 82.07%. This figure is interpreted as the value of a good competence.